2021
DOI: 10.3390/diagnostics11020211
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Ultrasound as Helpful Tool in Polyneuropathies

Abstract: Background: Polyneuropathies (PNP) are a broad field of diseases affecting millions of people. While the symptoms presented are mostly similar, underlying causes are abundant. Thus, early identification of treatable causes is often difficult. Besides clinical data and basic laboratory findings, nerve conduction studies are crucial for etiological classification, yet limited. Besides Magnetic Resonance Imaging (MRI), high-resolution nerve ultrasound (HRUS) has become a noninvasive, fast, economic and available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 155 publications
4
21
0
5
Order By: Relevance
“…However, this fraction might even be underestimated as high cutoff values for enlarged CSAs in comparison to other studies were applied 23 . Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64–89%) 24–26 . In our study, abnormalities on nerve ultrasound were observed in four out of seven patients with Sjögren's syndrome and clinical signs of neuropathy but without neurophysiologic evidence of neuropathy.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, this fraction might even be underestimated as high cutoff values for enlarged CSAs in comparison to other studies were applied 23 . Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64–89%) 24–26 . In our study, abnormalities on nerve ultrasound were observed in four out of seven patients with Sjögren's syndrome and clinical signs of neuropathy but without neurophysiologic evidence of neuropathy.…”
Section: Discussionsupporting
confidence: 77%
“…23 Nevertheless, comparable studies on patients with CIDP found pathologic ultrasound findings with similar frequencies (64-89%). [24][25][26] In our study, abnormalities on nerve ultrasound were observed in four out of seven patients with Sjögren's syndrome and clinical signs of neuropathy but without neurophysiologic evidence of neuropathy. This finding suggests that nerve ultrasound might give additional information on the existence of a Sjögren's syndrome-associated neuropathy in cases of nerve conduction studies failing to detect nerve damage.…”
Section: Discussionsupporting
confidence: 51%
“…Since UPSS scores have not yet been validated using independent samples, further studies assessing several additional nerve sites is warranted to refine the total score. In addition, various ultrasound scoring tools are available and have been shown applicable with high accuracy ( 1 , 26 ), tools in addition to UPSS should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…15 While enlargement is very focal in entrapments, tumors and trauma, it is diffuse, multifocal and more proximal in non-Hansen's polyneuropathies. 16,17 Therefore, the peculiar enlargement pattern identified in this paper appears unique to leprosy. Nagappa et al showed that the median nerve in leprosy was maximally enlarged proximal to wrist crease with gradual tapering proximally while it enlarged most at the distal wrist crease in carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 50%